Validation of the suppression ratio from a simplified EEG montage during targeted temperature management after cardiac arrest. (August 2020) - Riker, Richard R.; Craig, Alexa; Eubank, Louis; May, Teresa; Seder, David B.
Abstract: Aim: The Suppression Ratio (SR) estimates the percent of the electroencephalography (EEG) epoch with very low voltage, and is associated with neurological outcome after cardiac arrest. We aimed to compare the SR generated by two monitoring devices and determine the association between SR and patterns on amplitude integrated EEG (aEEG) and full conventional EEG (cEEG). Methods: Consecutive adult patients treated with TTM after cardiac arrest were enrolled. We compared the SR from the Medtronic Vista monitor (MSR) to the SR generated from the full montage cEEG with Persyst Magic-Marker software (PSR). A blinded neurologist, board certified in epilepsy, scored the 4-channel aEEG pattern and the cEEG background using standardized terminology. Values for SR were compared to aEEG and cEEG categories using Kruskal–Wallis ANOVA, and to each other using Altman-Bland methodology. Results: 23 adults treated with TTM had a mean core temperature of 33.8 °C at the time of SR and EEG background analysis. The MSR was 0% during continuous cEEG background, 23% when cEEG was discontinuous, and 64% during cEEG burst suppression ( p  = 0.01). The MSR was 0% during aEEG continuous patterns, 34% during aEEG burst suppression, and 46% during flat aEEG ( p  < 0.001). The MSR and PSR were highly correlated (0.88, p  < 0.0001), with minimal bias (0.3%) and excellent 95% limits of agreement (−2.9 to 2.4%). Conclusion: The Suppression Ratio from the Medtronic Vista monitor is highly correlated with the full montage SR from Persyst software. The MSR values are valid, changing with different aEEG patterns and cEEG background categories.